PTU-196 Long-term results of laparoscopic Heller's cardiomyotomy for achalasia cardia. (28th May 2012) - Stavrou, M; Martin, L; El-Madani, F; Gupta, S
Abstract : Introduction: To review the long-term efficacy of Laparoscopic Heller's Cardiomyotomy in patients with Achalasia Cardia at a large UK District General Hospital. Methods: A structured postal survey was undertaken on 40 consecutive patients with clinical, radiologic, endoscopic and manometric diagnosis of Achalasia Cardia who underwent Laparoscopic Cardiomyotomy by a single surgeon at our unit between 1996 and 2011. The procedure was supplemented by Anterior Fundoplication on all the patients. Results: The average age of the 40 patients in the study group was 49 years (range 18–80 years) with an equal sex distribution. Mean follow-up since surgery was 34 months (3–88 months). Dysphagia scores improved in all the patients (100%). Thirteen patients (33%) had complete remission from dysphagia whereas 24 (60%) experienced occasional dysphagia only. Despite the improvement in dysphagia, three patients (7%) continued to have regular dysphagic symptoms. Although only seven patients (17%) had regular reflux symptoms, fifteen patients (37%) were on regular acid-suppressing drugs. Results were further stratified into excellent (38%), good (37%), fair (25%) and poor (0%), based on a previously described classification. 1 All patients (100%) reported overall improvement in their health-related quality of life as evaluated by relief of gastrointestinal symptoms (dysphagia and reflux) and patient satisfaction. Patient satisfaction was considerably high largely due to the absence of dysphagia and undeterred by the presence of reflux symptoms. Conclusion: Laparoscopic Cardiomyotomy with Anterior Fundoplication achieves excellent long-term relief from dysphagia for most of the patients with Achalasia. Despite the fundoplication, acid reflux is a frequent post-operative complication. However anti-acid medications minimise its clinical significance. Competing interests: None declared. Reference: 1. Vantrappen G, Hellmans J. Treatment of achalasia and related motor disorders. Gastroenterology 1980;79 :144–5.